Gender, Attachment Patterns, and Mental Representations of Parents and Self as Predictors of Young Adolescents' Trauma Symptoms. (2nd October 2022) - Blum, Bryan; Goodman, Geoff; Rentrop, Carla; Malberg, Norka; Agrawal, Palakrajiv
ABSTRACT: While gender and attachment quality have been related to trauma symptomatology in young adolescents, another factor possibly related to trauma symptoms is quality of mental representations of close relationships. In this study, 109 eighth grade students ages 12–13 (44% female) were recruited from a private middle school for academically advantaged, ethnically diverse students over the course of four years, with each new group of participants providing data in the fall semester of their eighth grade year. Participants reported trauma symptoms and the affective valence of their mental representations of self and parents; school staff reported on participants' attachment patterns. Significant negative correlations existed between preoccupied attachment and affective valence of parental and self mental representations as well as significant positive correlations between incoherent/disorganized and preoccupied attachment, respectively, and childhood trauma symptoms. Overall, incoherent/disorganized attachment predicted avoidance and hyperarousal symptoms, while preoccupied attachment predicted reexperiencing symptoms. For girls, incoherent/disorganized attachment and negative affective valence of self mental representations were both predictive of childhood trauma symptoms, while preoccupied attachment predicted reexperiencing symptoms. These results indicate that therapists must take into account the quality of both attachment and mental representations for middle schoolers when treating childhood trauma symptoms.